Mabini’s Political Deism: A Glimpse of His True Decalogue - Rivas, Virgilio (Social Sciences and Development Review, 2015)
The following essay is an attempt to review, albeit, briefly, one of the founding documents of the Philippine revolution, Apolinario Mabini’s True Decalogue. Though not exhaustive and carries no pretension of historical proficiency, the essay rather seeks to situate the document within its internal hermeneutic structure, no doubt shaped in the background by the immediate demands of the revolution, as did the intellectual and political currents from out of Europe that reached the archipelago via commercial and trade routes in the early 18th century. Mabini later lamented the fall of the revolution which in many ways was anticipated by the open and subtle warnings of the True Decalogue in the face of circumstances as well as internal conflicts, betrayal and corruption that haunted its leadership and demoralized its many unsung heroes.In light of this unfinished revolution, the True Decalogue continues to appeal to our time. The following essay is an attempt to review, albeit, briefly, one of the founding documents of the Philippine revolution, Apolinario Mabini’s True Decalogue. Though not exhaustive and carries no pretension of historical proficiency, the essay rather seeks to situate the document within its internal hermeneutic structure, no doubt shaped in the background by the immediate demands of the revolution, as did the intellectual and political currents from out of Europe that reached the archipelago via commercial and trade routes in the early 18th century. Mabini later lamented the fall of the revolution which in many ways was anticipated by the open and subtle warnings of the True Decalogue in the face of circumstances as well as internal conflicts, betrayal and corruption that haunted its leadership and demoralized its many unsung heroes.In light of this unfinished revolution, the True Decalogue continues to appeal to our time.